Study On The Formation Of Granular Algae - Tan, Pei Chin (Universiti Sains Malaysia, 2018)
Microalgae can be used in biological wastewater treatment as it can survive harsh condition. Microalgae have also been identified as potential alternative resource for biofuel production. But there are significant disadvantages to both applications as the algae culture usually low in density and small in size. This causes the harvesting and separation processes of the microalgae to be energy-intensive and thus nonfeasibility of scale up. Microalgae are able to produce extracellular polymeric substances (EPS) which is crucial for the formation of granule. By providing cultural condition that is suitable for microalgae to form granule, harvesting and separation of microalgae will be much easier as granule has higher density and can settle down easily. In this experiment, several factors that influence the production of extracellular polymeric substances (EPS) in microalgae are investigated, which are the availability of nutrient and growth phase of the microalgae. MLSS, EPS content and nutrient analysis are carried out periodically throughout the experiment. There is formation of granular sludge in microalgae found after the growth of microalgae reach stationary phase. The settling time of the microalgae became shorter as bigger and more granule form.